2014
DOI: 10.1638/2013-0131r.1
|View full text |Cite
|
Sign up to set email alerts
|

PHARMACOKINETIC BEHAVIOR OF ENROFLOXACIN AND ITS METABOLITE CIPROFLOXACIN IN URUTU PIT VIPERS(BOTHROPS ALTERNATUS)AFTER INTRAMUSCULAR ADMINISTRATION

Abstract: Enrofloxacin is widely used in veterinary medicine and is an important alternative to treating bacterial infections, which play an important role as causes of disease and death in captive snakes. Its extralabel use in nontraditional species has been related to its excellent pharmacokinetic and antimicrobial characteristics. This can be demonstrated by its activity against gram-negative organisms implicated in serious infectious diseases of reptile species with a rapid and concentration-dependent bactericidal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…However, marked differences have also been reported within the reptile order (Papich, ). The present study has shown an average HL λz of E that is shorter than that reported in Trachemis turtles (47 h) (Giorgi et al ., ) and vipers (27 h) (Waxman et al ., ), similar to that reported in alligator (21 h after iv administration) (Helmick et al ., ), but higher than in pythons (6 h) (Young et al ., ), highlighting once again the importance of the species‐specific pharmacokinetic studies.…”
Section: Discussionsupporting
confidence: 90%
“…However, marked differences have also been reported within the reptile order (Papich, ). The present study has shown an average HL λz of E that is shorter than that reported in Trachemis turtles (47 h) (Giorgi et al ., ) and vipers (27 h) (Waxman et al ., ), similar to that reported in alligator (21 h after iv administration) (Helmick et al ., ), but higher than in pythons (6 h) (Young et al ., ), highlighting once again the importance of the species‐specific pharmacokinetic studies.…”
Section: Discussionsupporting
confidence: 90%
“…This raises the question of whether drug disposition may be significantly different between lizard and snake species. However, similar CL has been observed between geckos ( Agius et al., 2020 ), bearded dragons ( Salvadori et al., 2017 ) and rattlesnakes ( Waxman et al., 2015 ) in non-opioid drugs such as enrofloxacin. Thus, whether drug CL differs within the squamates likely depends on the drug of interest.…”
Section: Pharmacokinetic Datasupporting
confidence: 55%
“…that corroborated with the findings of Bennett (1991). Use of enrofloxacin was found to be effective to control bacterial infection as it has activity against gram-negative organisms implicated in serious infectious diseases of reptile species with a rapid and concentration-dependent bactericidal effect (Waxman et al, 2014). In this case meloxicam was used as NSAID, which works mainly peripherally decreasing prostanoids that facilitates the generation and conduction of pain impulses (Bouts and Gasthus, 2002).…”
Section: Discussionmentioning
confidence: 99%